The 40Ar(d, p)41Ar cross section between 3–7 MeV. (December 2022) - Bleuel, D.L.; Anderson, S.G.; Bernstein, L.A.; Brown, J.A.; Caggiano, J.A.; Goldblum, B.L.; Gordon, J.M.; Hall, J.M.; Harrig, K.P.; Johnson, M.S.; Laplace, T.A.; Marsh, R.A.; et al.
Abstract: To determine the safety of using argon as a deuteron beam stopping material, the   40 Ar(d, p) 41 Ar cross section was measured at average deuteron energies of 3.6 MeV, 5.5 MeV, and 7.0 MeV using an activation method. A 16-MeV deuteron beam produced by Lawrence Berkeley National Laboratory's 88-Inch Cyclotron was degraded to each energy by nickel foils and the front wall of an aluminum gas chamber. The reduced-energy deuterons were used to activate a sample of n a t Ar gas. After each irradiation, the gas chamber's   41 Ar activation was measured with a high-purity germanium detector. The cross sections measured were larger than a previous measurement by ∼ 40%. Highlights: We measured the 41 Ar(d, p) 40 Ar cross section at 3.6, 5.5 and 7.0 MeV using an activation method. Our measured cross section was significantly higher than both a previous measurement and TENDL. Without significant shielding, argon is not recommended as a deuteron beam stopping medium.